KONSEP PEDAGOGI HUMANIS PAULO FREIRE DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA BUDDHA - Tantra, Manggala Wiriya; Murtiningsih, Rr. Siti; Siswadi, Gede Agus (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
It is time for Indonesia's golden generation to be filled with talented human beings with humanist souls. Of course this is a challenge that is not easy to realize, so it is necessary to contribute thoughts in constructing the idea of humanist education so that it becomes a reality in the future. The purpose of this research is to examine Paulo Friere's humanist pedagogy and its relevance to Buddhist religious education. This research is expected to contribute comprehensive knowledge and ideas in building a humanism-based education system in Indonesia. This research uses literature study and Miles and Huberman analysis method to analyze the collected data, data reduction, data presentation, and in-depth conclusion drawing. The results of this study show that there is a relevance between Paulo Friere's pedagogy and Buddhist education, both of which emphasize the principle of humanism in educating without involving elements of oppression and focusing more on the learning process as the main key to understanding social reality. Both have strong similarities about the purpose of education that leads to critical awareness and enlightenment of students achieved as the ultimate goal of education. Both also have similarities in viewing the position of teachers and students as an equal relationship and both complement each other.